Clinical predictors of mortality in people with severe behavioral and psychological symptoms of dementia - Mendes, Aline; Herrmann, François R.; Bergh, Sverre; Cesana, Bruno Mario; Handels, Ron; Ciccone, Alfonso; Cognat, Emmanuel; Fabbo, Andrea; Fascendini, Sara; Frisoni, Giovanni B.; Frölich, Lutz; Jori, Maria Cristina; et al. (Journal of the American Medical Directors Association, 2025)
Objectives - Dementia significantly impacts quality of life, health care costs, and caregiver burden, being a leading cause of death among older adults. We investigated predictors of mortality in people with severe behavioral and psychological symptoms of dementia (BPSD). - Design - A multicentric longitudinal observational study was conducted, comprising clinical assessments at baseline and every 6 months for 3 years. - Setting and Participants - People with severe BPSD (Neuropsychiatric Inventory, NPI ≥32) living at home. - Methods - Data on demographics and clinical characteristics were collected at baseline and during 6-monthly follow-ups over 3 years. The main outcome was mortality, documented over a total period of 4 years and analyzed using the Cox proportional hazards model. - Results - Of the 508 patients with dementia with severe BPSD, 165 (32.5%) died during the 4-year follow-up. Non-survivors were older (79.8 ± 7.7 vs 77.3 ± 8.0; P < .001), more likely to be male (58.8% vs 38.5%; P < .001), and had higher BPSD severity (NPI: 57.2 ± 20.2 vs 50.3 ± 17.9; P < .001), lower cognitive function according to the Mini-Mental State Examination (MMSE) (13.5 ± 6.6 vs 16.4 ± 5.9; P < .001), and worse functional status according to the Alzheimer's Disease Cooperative Study - Activities of Daily Living Scale (ADCS) (28.8 ± 16.4 vs 36.3 ± 17.2; P < .001) at baseline. Significant predictors of mortality included male sex [hazard ratio (HR), 2.03; 95% confidence interval (95% CI), 1.46-2.82; P < .001], older age at diagnosis (HR, 1.05; 95% CI, 1.03-1.07; P < .001), higher NPI scores (HR, 1.01; 95% CI, 1.01-1.02; P = .002), lower MMSE (HR, 0.95; 95% CI, 0.93-0.98; P = .001), lower ADCS (HR, 0.98; 95% CI, 0.98-0.99; P = .015), and lower quality of life rated by proxy (HR, 0.97; 95% CI, 0.95-0.99; P = .021). The use of antidepressants (HR, 0.69; 95% CI, 0.48-0.98; P = .038) was associated with increased survival. Delusions (HR, 1.0; 95% CI, 1.03-1.12; P < .001), hallucinations (HR, 1.07; 95% CI, 1.02-1.11; P = .002), and agitation/aggression (HR, 1.05; 95% CI, 1.01-1.09; P = .021) were significantly linked to increased mortality. - Conclusions and Implications - Older age, male sex, severe BPSD, and lower cognitive and quality of life scores significantly predict increased mortality in patients with severe BPSD.